Optimasi Produksi Tanaman Padi dan Jagung di Kabupaten Pesisir Selatan Menggunakan Metode Fungsi Penalti Eksterior - Emmelia Safani; Devni Prima Sari (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Planted area, harvested area, and the average production of rice and maize in Pesisir Selatan Regency in 2010-2018 fluctuated, thus affecting agricultural conditions and the economy of the community and government. Therefore, it is necessary to have an optimal planting area, harvest area, and average production of rice and maize. The purpose of this study was to determine the form of a mathematical model and the results of the solution to optimize the production of rice and maize in Pesisir Selatan Regency with the exterior penalty function method. This research method explains the basic concept of the n-order polynomial regression method for the mathematical model of nonlinear programming problems and solving nonlinear programming problems with the exterior penalty function method. The exterior penalty function method converts a constrained nonlinear problem into a constrained one. The data used are secondary data obtained from the publication of the Puasat Statistics Agency for Pesisir Selatan Regency in 2010-2018. The optimal result of the exterior penalty function method for rice plant area is 66.667 Ha, the planted area of maize is 16.667 Ha, and the average total production of rice and maize is 236,56 Kw/Ha. Keywords — Production of Rice and Corn, Polynomial Regression Method, Exterior Penalty Function Method.